Private equity challenge - Elmos semiconductor se - capital structure - Wohlleben, Pauline (2023)
This paper presents an investment thesis on a hypothetical leveraged buyout of Elmos Semiconductor SE, a key player in the semiconductor industry known for its mixed-signal system solutions. With a strategic focus on automotive innovation, Elmos is positioned to benefit from the trends towards premiumization and electrification of vehicles. The thesis is underpinned by strategic acquisitions, workforce expansion and operational efficiencies. Valued at an EV/EBITDA multiple of 10.8x, Elmos represents a promising investment with an enterprise value of €1,756m. The analysis covers financial modeling, capital structure optimization and potential exit strategies and forecasts significant growth and returns for investors.